Simulation Technologies in Physics Learning for Education for Sustainable Development - Hanan Zaki Alhusni; Riski Ramadani; Titin Sunarti; Madlazim Madlazim (Journal of Innovative Technology and Sustainability Education, 2025)
Objective: This study aims to systematically analyse how simulation technologies are integrated into physics education to support Education for Sustainable Development (ESD). The objective is to identify publication trends, thematic focuses, and pedagogical implications of simulation-based learning in fostering sustainability competencies and scientific literacy. Method: A Systematic Literature Review (SLR) approach was employed using data from Scopus and ScienceDirect databases covering the years 2007-2025. Thirty-five selected articles were analysed using bibliometric mapping in VOSviewer and thematic content analysis to identify research patterns related to the use of simulation in ESD-oriented physics learning. Results: The findings reveal that simulation technologies enhance students' conceptual understanding, digital competence, and sustainability awareness. Four main themes emerged: (1) simulation for conceptual understanding, (2) sustainability competency development, (3) teacher digital competence, and (4) equity in virtual learning. Publication trends show a steady increase since 2019, with the highest research output in 2023. Most contributions originated from countries with strong digital infrastructures, such as the USA, Indonesia, and Switzerland. Novelty: This study provides an integrated view of simulation-based physics education as a driver of sustainability competencies, highlighting its dual cognitive and affective impact. Unlike previous reviews, this work explicitly connects simulation technology with ESD frameworks, offering insights for future pedagogical models and sustainable digital learning practices.